Estimation of Glomerular Filtration Rate from Plasma Clearance of 51-Chromium Edetic Acid. Issue 254 (August 1972) - Chantler, C.; Barratt, T. M.
Abstract : The glomerular filtration rate was estimated by a single compartment analysis of the rate of fall of plasma concentration of 51-chromium edetic acid after a single intravenous injection. This slope clearance consistently overestimated the simultaneously determined standard urinary clearance, but could be used to predict the latter with an accuracy of ±9% (95% confidence limits). The coefficient of variation of replicate estimates of the slope clearance in the same individual was 3·9%; thus two estimates of glomerular filtration rate by this technique which differ by 11% have a 95% probability of reflecting a genuine difference. The method requires an intravenous injection and blood samples at 2 and 4 hours; urine samples are not required. It is simple, safe, and precise, and is applicable to children.